Let's expand the products they are all in the form
![(a+b)(a-b)=a^2-b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%28a-b%29%3Da%5E2-b%5E2)
For the first one we have a=x and b=2i:
![(x+2i)(x-2i)=x^2-(2i)^2=x^2+4](https://tex.z-dn.net/?f=%28x%2B2i%29%28x-2i%29%3Dx%5E2-%282i%29%5E2%3Dx%5E2%2B4)
For the second one we have a=x-2 and b=2i:
![(x-2+2i)(x-2-2i)=(x-2)^2-(2i)^2 = x^2-4x+4+4=x^2-4x+8](https://tex.z-dn.net/?f=%28x-2%2B2i%29%28x-2-2i%29%3D%28x-2%29%5E2-%282i%29%5E2%20%3D%20x%5E2-4x%2B4%2B4%3Dx%5E2-4x%2B8)
For the third one we have a=x+1 and b=i:
![(x+1+i)(x+1-i)=(x+1)^2-i^2=x^2+2x+1+1=x^2+2x+2](https://tex.z-dn.net/?f=%28x%2B1%2Bi%29%28x%2B1-i%29%3D%28x%2B1%29%5E2-i%5E2%3Dx%5E2%2B2x%2B1%2B1%3Dx%5E2%2B2x%2B2)
The table is proportional, cause there all plus four.
-2 + 4 = 2
0 + 4 = 4
2 + 4 = 6
4 + 4 = 8
Hope it helps
Answer:
y = 7x + 22
Step-by-step explanation:
pretty self explanatory
hope this helps <3